2019
DOI: 10.1108/ebhrm-11-2018-0069
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of predicting employee performance through succession planning

Abstract: Purpose Leadership development practices develop future leaders for the organizations which are evidence for the proper utilization of organizational resources. The purpose of this paper is to integrate succession planning into the job demands–resources (JD–R) model to predict individual performance. Design/methodology/approach In total, 239 participants were drawn from commercial banks located in a large city of Pakistan through a structured questionnaire. The proposed model was tested through structural eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…Succession planning requires a successor who is competent and skilled in the leadership needs of the company. In today's marketplaces, a successful successor ensures that the business remains stable and viable (Ali & Mehreen, 2020;Santora & Bozer, 2015).…”
Section: Perspective Of Succession Planningmentioning
confidence: 99%
“…Succession planning requires a successor who is competent and skilled in the leadership needs of the company. In today's marketplaces, a successful successor ensures that the business remains stable and viable (Ali & Mehreen, 2020;Santora & Bozer, 2015).…”
Section: Perspective Of Succession Planningmentioning
confidence: 99%
“…The study outcome in Table 3 indicated that EE partially mediates the relationship between SPP and EP among academic staff of MPU. The result is guided by the study of Breevaart et al (2014), Ali and Mehreen (2019) and Gordon and Overbey (2018). Gordon and Overbey (2018) argued that in order to achieve institutional and individual goals, SPP helps to create talented staff members who are committed to their job.…”
Section: Discussionmentioning
confidence: 99%
“…Performance-driven employees are source of inspiration since they provide a predetermined path to gain a favorable or constructive evaluation of their skills and competences (Abdullahi et al , 2020; Ali and Mehreen, 2019). Succession planning practice (SPP) is indeed very crucial for the achievement of employee performance (EP) including organizational goals (Ali et al , 2014, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For individuals, it is critical to manage their career proactively due to the emergence of the self-career management perspective, which has created pressures on individuals to handle their careers by themselves (Ali, Mahmood, et al., 2019; Ali & Mehreen, 2019; Wessel et al., 2003). Such pressures have resulted in potential career shocks (Akkermans et al., 2018).…”
Section: Introductionmentioning
confidence: 99%